A Firm's-Eye View of Commercial Policy and Fiscal Reforms in Cameroon - Gauthier, Bernard; Soloaga, Isidro; Tybout, James (Washington, DC: World Bank, 2014)
After decades of high trade restrictions, fiscal distortions, and currency overvaluation, Cameroon implemented important commercial and fiscal policy reforms in 1994. Almost simultaneously, a major devaluation cut the international price of Cameroon's currency in half. This article examines the effects of those reforms on the incentive structure faced by manufacturing firms. Did the reforms create a coherent new set of signals? Did they reduce dispersion in tax burdens? Was the net effect to stimulate the production of tradable goods? The results of applying a cost function decomposition to detailed firm-level panel data suggest that the reforms created clear new signals for manufacturers, as effective protection rates fell by 80 to 120 percentage points. In contrast, neither the tax reforms nor the devaluation had a major systematic effect on profit margins. The devaluation did shift relative prices dramatically in favor of exportable goods, causing exporters to grow relatively rapidly.